Allgrove syndrome in endocrinology: Difficulties of diagnosis and treatment features. Case report - Uliana V. Buyvalenko; Anna R. Levshina; Anna K. Eremkina; Kseniya A. Komshilova; Nadezhda M. Platonova (Терапевтический архив)
Allgrove syndrome is a rare autosomal recessive disorder characterized by the achalasia, alacrimia, adrenal insufficiency, which gave the additional and more recognizable name of this pathology – “Triple-A syndrome”. The clinical presentation of classical signs and symptoms of the syndrome is dependent on the age of the patient. Ophthalmological abnormalities are usually present at birth, whereas adrenal and gastrointestinal abnormalities are apparent after six months to the first decade of life. Neurological dysfunction from the involvement of central or autonomic nervous systems is also common with Allgrove syndrome observed during the adolescent period. Genetic analysis and detection of the AAAS gene mutation is the main step in the diagnosis of the syndrome. The presented clinical case will demonstrate the difficulties in making a diagnosis, choosing a treatment strategy for a patient with a long history of Allgrove syndrome.